Protective effect of spermine against pentylenetetrazole kindling epilepsy induced comorbidities in mice. (July 2017) - Kumar, Mandeep; Kumar, Puneet
Highlights: Cognitive impairment and depression is common symptoms of epileptic patients. Increased nitric oxide level contributes to lower seizure threshold. PTZ kindling induced seizures is well known model for epilepsy in mice. Spermine prevented seizure occurrence, memory impairment and depressive symptoms. Spermine posses' anti-oxidant and nitric oxide modulation property. Abstract: Nitric oxide (NO), an important intracellular signaling molecule is involved in modulation of neuronal transmission. The NO level increases during epileptic activity in animal models of epilepsy. However, its role in epileptic activity remains controversial. Spermine is an endogenous polyamine; possesses anti-oxidant property and has ability to modulate ion channels and NO synthase activity. Therefore, the present study was designed to investigate the role of NO pathway in the neuroprotective effect of spermine, in Pentylenetetrazol (PTZ) induced kindling epilepsy in mice. PTZ (35 mg/kg; intraperitoneal, i.p.) was administered on every alternate day up to 29 days and challenge test was performed on 33rd day. From 15th day, spermine (5 and 10 mg/kg; i.p.), L-NAME (10 mg/kg; i.p), l -Arginine (50 mg/kg; i.p) and sodium valproate (400 mg/kg; i.p.) were administered up to 33rd day. Animals were sacrificed on 34th day for estimation of biochemical and neurotransmitters. Pretreatment with spermine, considerably, reversed the PTZ induced alterations. Further, pretreatment of L-NAME andl -Arginine with 5 and 10 mg/kg; i.p. spermine, respectively, leads to an increase and decrease in its protective effects. The present study suggests the involvement of NO pathway in the protective effect of spermine against PTZ-induced kindling epilepsy in mice.